2015
DOI: 10.1002/adma.201503448
|View full text |Cite
|
Sign up to set email alerts
|

Complementing Graphenes: 1D Interplanar Charge Transport in Polymeric Graphitic Carbon Nitrides

Abstract: Charge transport in polymeric graphitic carbon nitrides is shown to proceed via diffusive hopping of electron and hole polarons with reasonably high mobilities >10(-5) cm(2) V(-1) s(-1). The power-law behavior of the ultrafast luminescence decay exhibits that the predominant transport direction is perpendicular to the graphitic polymer sheets, thus complementing 2D materials like graphene.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

18
184
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 181 publications
(204 citation statements)
references
References 51 publications
18
184
0
2
Order By: Relevance
“…Thei nsufficient charge separation may stem from the fact that the current growth methods usually lead to an unordered layered structure with large grain boundaries. [7] This study showed that if the CN layers are close and ordered enough, the electron and hole mobility is significantly enhanced. [7] This study showed that if the CN layers are close and ordered enough, the electron and hole mobility is significantly enhanced.…”
mentioning
confidence: 83%
See 1 more Smart Citation
“…Thei nsufficient charge separation may stem from the fact that the current growth methods usually lead to an unordered layered structure with large grain boundaries. [7] This study showed that if the CN layers are close and ordered enough, the electron and hole mobility is significantly enhanced. [7] This study showed that if the CN layers are close and ordered enough, the electron and hole mobility is significantly enhanced.…”
mentioning
confidence: 83%
“…Furthermore,b ecause the electron and hole mobility within the CN layer is perpendicular to the 2D layer (unlike in graphene), [7] the ordered sheet structure with closer layer distance should augment the electron and hole mobility. Theg ood hole-extraction properties can be attributed to the low recombination rate,f ewer defect sites,a sw ell as al ayer porosity that is sufficient for good electrolyte penetration.…”
Section: Angewandte Chemiementioning
confidence: 99%
“…This allows one to obtain an unbiased estimate, which is highly desirable, since experimental results indicate high exciton mobilities in the z-, or interlayer, direction. 72 However, there is an additional ambiguity when comparing WM with BSE@GW results: conventionally, the WM model includes the "vibrational" contribution to the dielectric constant, which lowers the exciton binding energy and thus increases the optical band gap. In BSE@GW, in contrast, these effects are not included, since they would either require thermal sampling or excited state geometries.…”
Section: Confronting Wm Experiments and Gwmentioning
confidence: 99%
“…140 It should be noted however, that the explanation for the increased activity is not as simple as just being caused by the increased amount of active sites at an increased surface area, but also the higher amount of amine functionalities, increased charge carrier stability and an optimized packing of the polymer layers have been identified as playing a crucial role. 141,142 In addition, very often co-monomers, e.g. with other heteroatoms than nitrogen have been added to the carbon nitride synthesis to tailor the band gap by the formation of copolymers or heteroatom-doped carbon nitrides.…”
Section: Cmps For Photocatalytic Hydrogen Evolutionmentioning
confidence: 99%